Zipora Cochavi-Raine y, The Alashia Texts from the 14th and 13th Centuries BCE. A Textual and Linguistic Study, Münster, Ugarit-Verlag, 2003, Alter Orient und Altes Testament (AOAT) 289. xiv + 129 pp. EUR 56,- ISBN 3- 934628-17-6 - Gestoso Singer, Graciela (2007)
Fil: Gestoso Singer, Graciela N. Pontificia Universidad Católica Argentina; Argentina